Multi‐Model Assessment of the Role of Anthropogenic Aerosols in Summertime Climate Change in Europe - P. Nabat; S. Somot; J. Boé; L. Corre; E. Katragkou; S. Li; M. Mallet; E. vanMeijgaard; V. Pavlidis; J.‐P. Pietikäinen; S. Sørland; F. Solmon (Geophysical Research Letters)
Abstract Global and regional climate models (respectively GCMs and RCMs) are delivering conflicting messages about summertime climate change in Europe, revealing notably a weaker warming in RCMs. A dedicated multimodel ensemble of nine GCM‐RCM pairs is analyzed to assess the role of anthropogenic aerosols in these inconsistencies. The expected decrease of anthropogenic aerosol concentrations is found both to modify the future evolution of shortwave radiation and to generate an extra warming. For every tenth in aerosol optical depth drop in Central Europe, shortwave radiation is increased at the surface by 6.3 Wm−2 and decreased at the top of the atmosphere by 5.6 Wm−2, while near‐surface temperature is increased by 0.3°C. The consideration of time‐varying anthropogenic aerosols in RCMs thus contributes to improving GCM/RCM consistency in Europe for these three variables, but not for water cycle. The results obtained underline the necessity to better consider aerosols in upcoming regional climate simulations.